How to use the reader's guide [videorecording] (Bronx, N.Y. H.W. Wilson, 1987)
Introduces students to the basic research skills they need to locate articles through the use of the reader's guide. Demonstrates the use of subject headings, subheadings, and author's name.
Keywords: Reader's guide to periodical literature; Libraries and readers; Library science